Year-end Review and Prospects: A View from Congress - Payumo, Felicito C. (Kasarinlan: Philippine Journal of Third World Studies; Vol 10 No 2 (1994): Rethinking the State and the Economy 2, 2008)
The Ramos administration made great strides in the economic field. The economic growth was real; it did not only consist of public expenditure but also of investments. However, is it quality growth or will it go bust, as it did in the past? This paper contends that the growth will not recede, given that the necessary structural reforms were made in order to sustain this growth. How and why did the Ramos administration succeed in implementing these reforms when its predecessors failed to do so? This paper attributes this success to what critics call two unlikely factors: first, the president's penchant for micromanagement, and second, a reformist congress. Despite the successes of the Ramos administration, beyond entitlements and social welfare, productivity, income distribution, and unemployment still need to be addressed in order to make economic growth benefit every Filipino.